1990
DOI: 10.1007/bf00006352
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eyestalk ablation on haemolymph osmotic and ionic concentrations during acute salinity exposure in the freshwater shrimp Macrobrachium olfersii (Wiegmann) (Crustacea, Decapoda)

Abstract: The effect of bilateral eyestalk ablation on haemolymph osmotic and Na + , Cl-, K , Mg 2 + and Ca 2 + concentrations was investigated in the freshwater shrimp Macrobrachium olfersii during acute exposure (1, 3, 6, 12 and 24 h) to sea-water of 21%o S. Analysis of variance treatment indicated that haemolymph osmotic and Na', Cl-, K , Mg 2 + and Ca 2 + concentrations were affected by exposure time (p < 0.01). However, only [Na + ] was affected by eyestalk ablation (p < 0.01), destalked shrimps exhibiting haemolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
16
0
3
Order By: Relevance
“…In fact, they are smaller than in the limnic congener P. pandaliformis. However, they are larger than in M, oversii, which is frequently encountered several kilometers upstream in rivers and mountain streams (McNamara and Moreira, 1987;L6pez and Pereira, 1994). The difference in egg size between the two species of Macrobrachium is difficult to explain in this context, since these shrimps have a similar ecology.…”
Section: Egg Sizementioning
confidence: 83%
See 2 more Smart Citations
“…In fact, they are smaller than in the limnic congener P. pandaliformis. However, they are larger than in M, oversii, which is frequently encountered several kilometers upstream in rivers and mountain streams (McNamara and Moreira, 1987;L6pez and Pereira, 1994). The difference in egg size between the two species of Macrobrachium is difficult to explain in this context, since these shrimps have a similar ecology.…”
Section: Egg Sizementioning
confidence: 83%
“…In contrast, all fresh-water palaemonids investigated here are known to develop through the first larval stage in the absence of food: Z? pandaliformis (see Bakker, 1989), M. oversii (see Moreira et al, 1979;McNamara et al, 1980), M. carcinus (see Choudhury,197 la), M. acanthurus (see Choudhury,197 1 b). This gives the larvae sufficient time to leave freshwater streams or rivers, where strong water currents may prevail and plankton production is low.…”
Section: Egg Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vivo experiments conducted on different species of shrimps (Nagabhushanam and Jyoti, 1977;McNamara et al, 1990), crayfishes (Kamemoto et al, 1966;Kamemoto and Ono, 1969;Kamemoto and Tullis, 1972) and crabs (Kamemoto et al, 1966;Kamemoto and Ono, 1969;Kato and Kamemoto, 1969;Kamemoto and Tullis, 1972;Heit and Fingerman, 1975;Davis and Hagadorn, 1982) have shown that eyestalk ligation or ablation increased water influx and decreased hemolymph osmolality and/or ions (Na + , Cl -) concentration in animals acclimated to low salinities. In eyestalkless crustaceans, the decrease in osmolality and hemolymph ion concentrations could be due to: (1) a higher influx of water resulting from an alteration in the permeability of the teguments, (2) a greater loss of ions by an increase of permeability and/or a modification of the active ion uptake mechanisms and/or an increase in urine production, (3) a modification of the drinking rate and/or (4) a modification of the function of aquaporins (if they exist in crustaceans) caused by the absence of an eyestalk factor.…”
Section: Effects Of Eyestalk Ablation On Osmoregulatory Parametersmentioning
confidence: 99%
“…Devido à sua relativa abundância e grande importância econômica, pelo alto potencial na aquicultura e utilização na pesca artesanal e comercial (Sawaya, 1946;Bowles et al, 2000;Murphy & Austin, 2005;Valenti & Tidwell, 2006;Valencia & Campos, 2007), algumas espécies do gênero têm sido objeto de pesquisas que abrangem estudos sobre fisiologia e biologia (McNamara et al, 1985;McNamara et al, 1990;Müller & Prazeres, 1992;Lima et al, 1997;Müller et al 1999), reprodução (Ammar et al, 2001;Mossolin & Bueno, 2002), desenvolvimento morfológico e larval (Dugger & Dobkin, 1975;Lima et al, 1997;Gamba, 1982;Pereira & Garcia, 2002;Mossolin & Bueno, 2003;Müller et al, 2003;Anger & Hayd, 2009;Pantaleão et al, 2011), comportamento, biologia de populações e ecologia (Barki et al, 1991;Jalihall et al, 1993;Ammar et al, 2001;Bauer & Delahoussaye, 2008;Chen et al, 2009).…”
unclassified